L-Leucine Improves Metabolic Disorders in Mice With in-utero Cigarette Smoke Exposure - Zeng, Yunxin; Huang, Taida; Wang, Nan; Xu, Yi; Sun, Chunhui; Huang, Min; Chen, Chun; Oliver, Brian G.; Yi, Chenju; Chen, Hui (Frontiers in Physiology, 2021)
Objectives: Maternal cigarette smoke exposure (SE) causes intrauterine undernutrition, resulting in increased risk for metabolic disorders and type 2 diabetes in the offspring without sex differences. L-leucine supplementation has been shown to reduce body weight and improve glucose metabolism in both obese animals and humans. In this study, we aimed to determine whether postnatal L-leucine supplementation in female offspring can ameliorate the detrimental impact of maternal SE. Methods: Female Balb/c mice (6-week) were exposed to cigarette smoke (SE, 2 cigarettes/day) prior to mating for 5 weeks until the pups weaned. Sham dams were exposed to air during the same period. Half of the female offspring from the SE and SHAM dams were supplied with L-leucine via drinking water (1.5% w/w) after weaning (21-day) for 10 weeks and sacrificed at 13 weeks (adulthood). Results: Maternal SE during pregnancy resulted in smaller body weight and glucose intolerance in the offspring. L-leucine supplement in Sham offspring reduced body weight, fat mass, and fasting blood glucose levels compared with their untreated littermates; however somatic growth was not changed. L-leucine supplement in SE offspring improved glucose tolerance and reduced fat mass compared with untreated littermates. Conclusions: Postnatal L-leucine supplement could reduce fat accumulation and ameliorate glucose metabolic disorder caused by maternal SE. The application of leucine may provide a potential strategy for reducing metabolic disorders in offspring from mothers who continued to smoke during pregnancy.